2001
DOI: 10.1272/jnms.68.405
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Pyuria in Diabetic Women.

Abstract: The aim of the present study was to determine the prevalence of and the host factors for asymptomatic pyuria (ASP) in women with type 2 diabetes. The study included 179 type 2 diabetic women and consecutive 455 non-diabetic women attending as out-patients in 1996. Patients with symptoms of a urinary tract infection were excluded. ASP was defined as the presence of more than 10 leukocytes/high-power field in a random urine sample. Diabetic women more often had ASP than non-diabetic women (27.9 vs. 15.8%, P<0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Next, we evaluated pyuria as a risk factor for ASBU. Pyuria is considered significant at more than 10 leukocytes per mm of urine [ 22 ]. Our study indicates no association between ASBU and pyuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we evaluated pyuria as a risk factor for ASBU. Pyuria is considered significant at more than 10 leukocytes per mm of urine [ 22 ]. Our study indicates no association between ASBU and pyuria.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates no association between ASBU and pyuria. Only 14 cases had pyuria, and interestingly, 19 controls also reported pyuria [ 22 ]. The finding that pyuria is not significantly associated with ASBU implies the absence of inflammation in ASBU, which contrasts with symptomatic UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the prevalence of asymptomatic leukocyturia (ASL) is higher in women with diabetes than in those without diabetes, and these diabetic complications, especially neuropathy, are factors contributing to the development of ASL in diabetic women. 4 In addition, we recently demonstrated a relationship between ASL and impairment of the parasympathetic nervous system in women. 5 On the other hand, N-acetyl-β-D-glucosaminidase (NAG) is a widely distributed lysosomal enzyme with a molecular weight of 130,000-140,000 Da, located predominantly in renal proximal tubules.…”
Section: Introductionmentioning
confidence: 95%